2020
DOI: 10.7150/jca.31406
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanism of Metabolic Remodeling in Lung Cancer

Abstract: Metabolic remodeling is a key phenomenon in the occurrence and development of tumors. It not only offers materials and energy for the survival and proliferation of tumor cells, but also protects tumor cells so that they may survive, proliferate and transfer in the harsh microenvironment. This paper attempts to reveal the role of abnormal metabolism in the development of lung cancer by considering the processes of glycolysis and lipid metabolism, Identification of the molecules that are specifically used in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 119 publications
1
24
0
Order By: Relevance
“…Because we now know the potential role of uric acid in cancer initiation and progression, there may also be uric acid-lowering drugs, which have the potential for treating cancer. It has been reported that metabolic remodeling plays an important role in the evolution of some cancers [65], so targeting different mechanisms in carcinogenesis using uric acid is consistent with the findings that uric acid lowering drugs are able to exert anticancer effects.…”
Section: Uric Acid-lowering Therapy and Its Ability To Lower Cancer Risksupporting
confidence: 85%
“…Because we now know the potential role of uric acid in cancer initiation and progression, there may also be uric acid-lowering drugs, which have the potential for treating cancer. It has been reported that metabolic remodeling plays an important role in the evolution of some cancers [65], so targeting different mechanisms in carcinogenesis using uric acid is consistent with the findings that uric acid lowering drugs are able to exert anticancer effects.…”
Section: Uric Acid-lowering Therapy and Its Ability To Lower Cancer Risksupporting
confidence: 85%
“… 4 The phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) and mitogen-activated protein kinase kinase (MEK)/extracellular-regulated protein kinase (ERK)/5′ AMP-activated protein kinase (AMPK) pathways participate in the metabolic reprogramming of lung cancer, affecting endogenous fatty acid metabolism, glycolysis, and the tricarboxylic acid cycle and activating the proliferation, invasion, and metastasis of lung cancer as a result. 5 , 6 Metabolic reprogramming is becoming an important feature of tumor biology.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic reprogramming is one of the hallmarks of cancer ( Faubert, Solmonson & DeBerardinis, 2020 ), which takes place from the onset and throughout the development of cancer ( Chang, Fang & Gu, 2020 ). It plays an important role in the progression, metastasis, depressed immunity, and therapy resistance of cancer ( Lane, Higashi & Fan, 2019 ).…”
Section: Introductionmentioning
confidence: 99%